Ethnicity amongst second generation Sikh girls: a case study in Nottingham - Drury, Beatrice Denis (1988)
I examine the cultural lives, social relationships and ethnic identities of 16 to 20 year old Sikh females in Nottingham. Using an interview schedule, I interviewed my respondents individually and, in private.